INTENSIFIKASI PEMUNGUTAN PENDAPATAN DAERAH PADA DINAS PERHUBUNGAN KOTA BANDUNG - Engkus; Fitri Pebriani Wahyu; Chindi Permata Sari (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
This study discusses how the Regional Revenue Collection Intensification is carried out by the Bandung City Transportation Service Terminal UPTD. Terminal levies are a type of regional levies that have the potential and provide substantial input to increasing the local revenue of the city of Bandung, besides that the city of Bandung is a large city that has made progress in terms of the economy and in terms of social life, so that the mobility of the people of the city of Bandung is quite high, in terms of support it. then transportation is an important means of supporting the success of development. So, it is hoped that there will be an increase in the realization of regional fees in the city of Bandung. The point is to find out, describe, and analyze the implementation, constraints, and efforts to resolve the Terminal Levy Intensification. The research method used is a qualitative approach with qualitative descriptive methods, and primary and secondary data are obtained through data collection techniques, namely observation, interviews, and documentation. The results of the research with reference to the intensification of local revenue generation carried out by the Bandung City Transportation Service Terminal Technical Implementation Unit has not been carried out properly, as seen in the dimensions of expanding the revenue base, cost efficiency and reducing acquisition costs and increasing revenue capacity has not implemented properly because there are indicators that have not been fulfilled.